Curriculum Merdeka Concept Based on The Perspectives of John Dewey’s Progressivism Philosophy - Sri Sulis Kurniawati (Samudra Publisher, 2024)
Education can create the creative and innovative knowledge because it is always updated. Education also aims to improve skills, build character, educate people's lives, and improve the quality of life and human dignity in Indonesia. One way to perfect the concept of the national education system is through a progressive approach. The purpose of this study is to review the literature review of several research findings that have been published in a journal related to the philosophical view of John Dewey's progressivism which was carried out on the independent learning curriculum of the independent campus. Based on the literature review, it was found that the role of independent learning in universities is very important in the development of the Indonesian educational community. This is because independent learning on an independent campus is one form of accelerating the response to educational and globalization problems. This is also in line with the very influential tendency of progressivism, which requires rapid change.